2007
DOI: 10.3177/jnsv.53.90
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Administration of Plant-Derived Anthocyanin-Rich Colors to Spontaneously Hypertensive Rats

Abstract: SummaryAnthocyanins have beneficial effects such as free radical scavenging activity. We investigated the effects of continuous administration of colors from purple corn (PCC), purple sweet potato (PSC) and red radish (RRC) to spontaneously hypertensive rats (SHR). These are rich in anthocyanins. Animals were fed with diets containing PCC, PSC or RRC (1 mass% of diets) for 15 wk. While the body weight and the daily food intake of administered rats were not different from those of the non-administered control r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 17 publications
1
37
0
1
Order By: Relevance
“…There are different plant extracts examined on the hypotensive effects. Traditional herbal extracts 18 , blueberry 22 , cocoa 20 , purple corn, purple sweet potato and red radish 19 are some examples. A Brazilian folk medicine Cecropia glaziovii Sneth has reduced the mean systolic blood pressure by 20 mm Hg after 2 weeks of treatments where the single dose treatments of the extracts had not exerted any difference 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are different plant extracts examined on the hypotensive effects. Traditional herbal extracts 18 , blueberry 22 , cocoa 20 , purple corn, purple sweet potato and red radish 19 are some examples. A Brazilian folk medicine Cecropia glaziovii Sneth has reduced the mean systolic blood pressure by 20 mm Hg after 2 weeks of treatments where the single dose treatments of the extracts had not exerted any difference 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated their antihypertensive effects under in vitro conditions. The mechanisms of actions of flavonoids include functioning as ACE inhibitors 18 , antioxidant activity and vasorelaxation 19 . In the current study, 0.5 g of APE kgG 1 of body weight, was incorporated as the daily dose which contained 25 mg of total polyphenols where the majority (around 20 mg) were flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence shows that foods containing high concentrations of anthocyanins, such as blueberries, purple grapes, and corn, are more effective at reducing the risk of cardiovascular disease, particularly with respect to antioxidant and antiinflammatory effects (1)(2)(3)(4). We previously demonstrated that the anthocyanin-rich black rice pigment fraction and extracts significantly ameliorated atherosclerotic plaque progression in apoE-deficient (apoE 2/2 ) 6 mice (5-7).…”
Section: Introductionmentioning
confidence: 96%
“…The anthocyanins from purple sweet potato (PSP) are more stable than those from strawberry, red cabbage, perilla and other plants (Bolı´var et al 2004). Many researches reported PSP anthocyanins could scavenge free radical (Suda et al, 2002;Kano et al, 2005;Saigusa et al, 2005), attenuate liver dysfunction (Suda et al, 1997(Suda et al, , 1998Han et al, 2007), enhance memory function (Cho et al, 2003;Wu et al, 2008), inhibit mutagenicity (Yoshimoto et al, 1999), decrease high blood sugar (Matsui et al, 2002;Matsui et al, 2004) and lower high blood pressure (Shindo et al, 2007), and could also induce apoptosis of cancer cells (Hayashi et al, 2006) or inhibit cancer cell growth (Hagiwara et al, 2002;Wang et al, 2006), and other functions (Hayashi et al, 2003).…”
Section: Introductionmentioning
confidence: 98%